Magnetic macro drivers of labor efficiency: a study of high and low trade open economies - Suleman, Shahida; Bibi, Safia; Azam, Muhammad; Mohd Thas Thaker, Hassanudin; Cheong, Calvin W. H (Emerald Publishing, 2025)
This research aims to systematically compare the impact of macro drivers on labor efficiency (LEFF) in high and low trade openness economies, employing the Solow model as the theoretical framework. This study examines the influence of macro drivers on LEFF from 1995 to 2020, employing advanced panel regression methods such as stepwise regression (SR), fully modified ordinary least squares (FMOLS) and panel OLS. It utilizes Pedroni and Johansen co-integration tests to assess long-term dynamics and Granger causality tests to explore causal relationships between macro drivers and LEFF. The results reveal both long-term and short-term relationships between LEFF and the macro drivers: gross capital formation (GCF), per capita income (PCI), foreign direct investment (FDI), trade openness (TOP) and gross national savings (GNS). The findings show that these macro drivers positively and significantly influence LEFF in both high and low TOP economies. Specifically, FDI, PCI and GNS have a more substantial positive impact on LEFF in low TOP economies, while GCF and TOP have a greater influence in high TOP economies. Furthermore, in high TOP economies, FDI, TOP and PCI exhibit a unidirectional relationship with LEFF, while GNS and GCF show a bidirectional relationship. In low TOP economies, all five macrodrivers exhibit bidirectional relationships with LEFF. This research focuses on countries with high and low TOP, limiting the generalizability of its findings to other economic systems due to the unique trade, institutional and governance frameworks of these two distinct groups. To the best of the authors’ knowledge, this study is the first to compare the impact of theoretical macro drivers on LEFF across groups of countries differentiated by their degrees of TOP (high and low).